Dualisme Kebijakan Keamanan Nuklir Korea Utara Melalui Uji Coba Rudal Antar Benua Tahun 2021-2022 - Alunaza, Hardi; Ernianda, Annisa; Ilmah, Daris Nurul (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2024)
In 2021-2022, North Korea's nuclear developments surprised public. The testing of missiles over the past year produced the latest advanced nuclear. North Korea developing new an intercontinental nuke called "Hwasong-17". This article will discuss the dualism of nuclear policy carried out by North Korea through intercontinental missile tests to increase the national security in 2021-2022. The research focuses on two discussions. First, the movement of intercontinental nuclear tests and the response from world community. Second, the dualism policy impact for North Korea towards The Country's security. This article contain the Offense-Defense Theory, Nuclear Deterrence Concept with qualitative approach and descriptive research methods. The results of this article is to aim the impacts of North Korea's nuclear policy which used as main military strategy to maintain the country's security in positive and negative perspective